2013
DOI: 10.1645/ge-3203.1
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Characterization ofOrtleppascarisSp. Larvae, Parasites of the Cane ToadRhinella marinafrom Eastern Amazonia

Abstract: This study presents a new record for the occurrence of larval Ortleppascaris sp.(Sprent, 1978). The nematodes were collected from inside fibrous cysts found in the livers of cane toads, Rhinella marina (Linnaeus, 1758), captured in eastern Brazilian Amazonia. This is the first record of Ortleppascaris sp. larvae in both Brazil and this amphibian host, increasing its distribution in South America as well as expanding the number of helminths known to infect this toad. The detailed description of Ortleppascaris s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…As adults, these parasites are found in the gastrointestinal tract of Crocodilians (Goldberg et al, 1991), and in their larval form, they are found in the liver of amphibians (Moravec and Kaiser, 1995; González and Hamann, 2006, 2007), including Rhinella marina in Brazil, as previously described by Silva et al (2013a).…”
Section: Introductionmentioning
confidence: 81%
“…As adults, these parasites are found in the gastrointestinal tract of Crocodilians (Goldberg et al, 1991), and in their larval form, they are found in the liver of amphibians (Moravec and Kaiser, 1995; González and Hamann, 2006, 2007), including Rhinella marina in Brazil, as previously described by Silva et al (2013a).…”
Section: Introductionmentioning
confidence: 81%
“…larvae had already been reported parasitizing Prismantis cf. terraebolivaris (Moravec & Kaiser, 1995), from Tobago, Leptodactylus bufonius and Rhinella fernandezae Gonzalez & Hamann, 2007) in Argentina and Rhinella marina in Belém, Brazil (Silva et al, 2013), while the adult nematodes were reported parasitizing the intestines of crocodilians (genera Crocodylus, Caiman and Alligator) (Sprent, 1978;Goldberg et al, 1991;Waddle et al, 2009). Although the life cycle of these nematodes is yet to be known, the presence of these larvae in anurans suggests that the infection route for these helminths is through the ingestion of the prey, which indicates that the anurans participate as potential intermediate/paratenic hosts.…”
Section: Discussionmentioning
confidence: 99%
“…There have been reports that the nematode O. sinensis can cause superficial ulcers in the mucous layer and granulomatous inflammation in the submucous layer on the entire gastric walls of the Alligator sinensis infected with nematode O. sinensis (Zhao et al, 2015). Ortleppascaris adults have been found in the stomachs and intestines of alligators and crocodiles (Tellez, 2013; Waddle et al, 2009; Zhao et al, 2016), and larvae have been found in the livers of amphibians (Moravce, 1995; e Silva et al, 2013) and the mesenteries and the body cavities of fishes and frogs infected in a natural manner in Africa and the USA (Huchzermeyer, 2003; Tellez, 2013). Fish, frogs and amphibians are the main foods consumed by crocodiles and alligators, which greatly increases the risk of nematode Ortleppascaris for crocodiles and alligators.…”
Section: Discussionmentioning
confidence: 99%